Freedom summer [videorecording (DVD)] - Nelson, Stanley, 1951- (PBS, 2014)
"In the hot and deadly summer of 1964, the nation could not turn away from Mississippi. Over 10 memorable weeks known as Freedom Summer, more than 700 student volunteers joined with organizers and local African Americans in a historic effort to shatter the foundations of white supremacy in one of the nation's most segregated states ... even in the face of intimidation, physical violence, and death"--Container.